Validation of an administrative claims coding algorithm for serious opioid overdose: A medical chart review. Issue 10 (4th September 2019) - Mountcastle, Sally B.; Joyce, Andrew R.; Sasinowski, Maciek; Costello, Nancy; Doshi, Snehal; Zedler, Barbara K.
Abstract: Purpose: A standardized definition for serious opioid overdose has not been clearly established for disease surveillance or assessing the impact of risk mitigation strategies. The purpose of this study was to use medical chart review to clinically validate a claims‐based algorithm to identify serious opioid overdose events. Methods: The algorithm for serious opioid overdose required an opioid poisoning or external cause ICD‐9‐CM code occurring within 1 day of (a) an adverse effect code for serious central nervous system or respiratory depression or (b) a mechanical ventilation or critical care CPT code. The claims coding algorithm identified a sample of 145 individuals 18 years or older among patients that presented to the emergency department of two large hospitals in metropolitan Atlanta, Georgia from January 2014 to August 2015. Claims‐defined cases were evaluated against rigorous clinical definitions for serious opioid overdose using (a) literature‐based criteria for typical clinical manifestations of opioid overdose and/or (b) clinical response to the opioid‐specific reversal agent naloxone. The positive predictive value (PPV) for a serious opioid overdose was calculated as the percentage of clinically confirmed cases (definite or probable). Results: Among 140 evaluable claims‐defined cases, 107 fulfilled clinical criteria for a serious opioid overdose [95 definite and 12 probable; PPV of 76.4% (95% CI 69.4%, 83.5%)]. Among 30 nonconfirmed cases, 20 were polyintoxications involving one or more nonopioid psychoactive agents. Conclusions: An administrative claims coding algorithm for serious opioid overdose had high clinical predictive performance in a medical chart review.